Exploring the Relationship of Mathematical Reasoning and Computational Thinking - Ferreira, Thiago Diniz; Santos, Jucelio Soares dos; Medeiros, Rosângela de Araújo; Andrade, Wilkerson L.; Brunet, João; Melo, Monilly Ramos Araujo (Anais do Workshop de Informática na Escola (WIE), 2023)
We investigated the relationship between Mathematical Reasoning and Computational Thinking in high school students. We used Screening Programming and Bebras as assessment tools to estimate the participants’ Mathematical Reasoning and Computational Thinking proficiency. Through the statistical analysis, we observed a robust and moderate correlation between these skills in students. Our findings suggest that the development of one skill can contribute to the improvement of the other and underscores the importance of considering these skills in an integrated manner during students’ education. This study’s findings provide relevant insights for planning instruction and learning strategies in the field of Computer Science while also fostering future research in diverse educational contexts.